Influence of some social and environmental factors on the nutrient intake and nutritional status of schoolchildren. Issue 2 (June 1975) - Jacoby, A; Altman, D G; Cook, J; Holland, W W; Elliott, A
Abstract : Only children had significantly higher intakes of many nutrients and nutrients/1000 kcal than other children. A higher proportion of only children was found to be obese. There were no significant differences according to birthrank in intakes by children. There were more obese children among the fatherless than those with fathers, in particular among those whose mothers were widowed. However, this was not accounted for by the present dietary findings, since fatherless children had lower intakes of carbohydrate and added sugar. There were no differences in nutrient intake or intake/1000 kcal by mother's country of origin or her level of education, or by disposable income.